(untitled) (Journal of Informatics Education and Research, 2025)
Although the organic sector is small, it has grown rapidly during the last decade. Concerned about the health, targeted consumers tend to choose organic agro products instead of conventional ones. This paper aims to find the factors affecting organic agro food producers and promotional strategies to improve their business performance in Bangalore. The research methods are composed of quantitative method that is the assessment of factors affecting and promotional strategies organic agro food producers. The study applied the convenient sampling method to collect the primary data from 100 producers and the study has framed the two objectives to fill the research gap & examining the factors that affect the organic food production and promotion. The study applied the discriminate analysis and the result indicated that better living condition and no chemical are found to be more effect on the organic food demand. The study examined the impact of operational strategies of organic agro food producers with the help of statistical tool of structural equation model. The study result reveals that the promotional strategy factors Pamphlets/ Advertisement in newspaper having the higher impact and followed by the Posters in supermarket or public places. This research will be useful to the organic food producers to improve their business performance.